Characterization, modeling and vibration control of a flexible joint for a robotic system. (April 2014) - Lessard, Joël; Bigras, Pascal; Liu, Zhaoheng; Hazel, Bruce
This paper presents the experimental characterization and vibration control of a flexible robotic system. For this work, a test bench was built to characterize the harmonic drive (HD) and joint components, while control algorithms were designed and compared to minimize vibration. Encoder accuracy was critical since the difference in the measurements between two encoders was used to evaluate the vibrational behavior of the test set-up. Therefore, a laser tracker was used to characterize the error of the output encoder. Real-time compensation using this technique achieved an angular position accuracy of 50 µrad. Four rosette strain gauges were fixed to the HD's flexible spline to determine its torsion. To reduce torque ripple, a real-time correcting function was applied. It was thus possible to reduce the error to 0.3% of the full-scale error. Two vibration control strategies were developed, namely, singular perturbation and feed-forward control. Simulation results showed that both control strategies greatly reduced vibration response compared to a common rigid control. However, test results showed that good vibration control could only be achieved with the feed-forward approach: the singular perturbation technique generated too much torque ripple to the motor. A feed-forward controller can quickly stabilize the link, achieving the same settling time as with the rigid control algorithm.